Little by Little - Stewart, Amber; Marlow, Layn (New York, NY : Orchard Books, 2008)
Otto is a young otter who can do many things well, but swimming is not one of them until his older sister tells him to start small and, little by little, he is able to reach his goal, adding swimming to his "I can do" list.